PELATIHAN DAN PENDAMPINGAN MEMBANGUN PRAKTIK DIGITAL MARKETING UNGGUL UNTUK PENINGKATAN PEMASARAN UMKM DI KOTA JAKARTA BARAT - Siti Mariam; Abdul Haeba Ramli (Indonesian Collaboration Journal of Community Services (ICJCS), 2023)
Increasing penetration of digital technology has given rise to the need to understand and implement effective marketing strategies, especially for Micro, Small and Medium Enterprises (MSMEs). This service activity aims to provide training and assistance to MSMEs in West Jakarta City in building superior Digital Marketing practices to increase their competitiveness and product marketing. The service implementation methodology involves a series of intensive training that covers basic Digital Marketing concepts, use of social media, search engine optimization, and other online marketing strategies. It is hoped that the results of this activity will provide MSMEs with a better understanding of the potential and benefits of digital marketing. Through practical assistance, it is hoped that MSMEs will be able to implement Digital Marketing strategies that are relevant to local market characteristics. Apart from that, this activity will also evaluate the impact of the training and mentoring on increasing sales and visibility of MSMEs in the digital realm. By involving MSME players as active partners, this activity is expected to make a positive contribution to local economic development in the City of West Jakarta. It is hoped that the findings from this activity can become the basis for developing similar training programs in other regions, so that MSMEs can continue to develop and compete effectively in this digital era